Role of investments in industrialization process for sustained economic - Chiemeke, Charles (2015)
In this research we investigate the potential benefits of investments in industrialization process for sustained growth on fifty six countries with special focus on Middle East and North African Region (MENA). This study applies the varying coefficient production frontier approach, a recently evolving technique that isolates catching up to the frontier (technical efficiency improvement) from shifts in the frontier (technical progress), to analyze the economic performance of developing countries of MENA. The results suggest that total factor productivity (TFP) contributes a minimal amount to the output growth in this region and the frontier estimations results also suggest that these countries do not achieve much progress compared to the rest of the world. However, some of the MENA countries seem to show a better growth performance than that of the averages in each sub period with respect to the rest of MENA.